2016
DOI: 10.1155/2016/8473242
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Colitis Is Attenuated by Cardioprotective Diet Supplementation That Reduces Oxidative Stress, Inflammation, and Mucosal Damage

Abstract: Inflammatory bowel diseases (IBD) such as ulcerative colitis (UC) and Crohn's disease (CD) are multifactorial, relapsing disorders of the gastrointestinal tract. However, the etiology is still poorly understood but involves altered immune responses, epithelial dysfunction, environmental factors, and nutrition. Recently, we have shown that the diet supplement corabion has cardioprotective effects due to reduction of oxidative stress and inflammation. Since oxidative stress and inflammation are also prominent ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 42 publications
1
7
0
2
Order By: Relevance
“…Among many features of IBD, a lack of equilibrium between oxidants and antioxidants is repeatedly reported. Moreover, a potential of antioxidant therapies, which could block tissue damage and reverse natural history of IBD, is increasingly recognized [17,18,19]. In continuation of our study on oxidative stress in IBD, here, we demonstrated the diminished systemic nonenzymatic antioxidant capacity, in terms of thiol stress and reduced serum uric acid concentrations as well as total antioxidant status levels.…”
Section: Discussionsupporting
confidence: 72%
“…Among many features of IBD, a lack of equilibrium between oxidants and antioxidants is repeatedly reported. Moreover, a potential of antioxidant therapies, which could block tissue damage and reverse natural history of IBD, is increasingly recognized [17,18,19]. In continuation of our study on oxidative stress in IBD, here, we demonstrated the diminished systemic nonenzymatic antioxidant capacity, in terms of thiol stress and reduced serum uric acid concentrations as well as total antioxidant status levels.…”
Section: Discussionsupporting
confidence: 72%
“…Inflammatory bowel disease is a chronic, repetitive and non-specific gastrointestinal inflammatory disease comprising two conditions: Ulcerative colitis (UC) and Crohn's disease ( 1 ). As a chronic intestinal disease, UC produces inflammatory reactions and immune response at the colonic mucosa ( 2 ), accompanied by weight loss, diarrhea and bloody stools ( 3 ). Long-term severe colitis is known to cause colorectal cancer ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenesis of IBD is complex and remains undetermined, being thought to result from an interaction between susceptibility genes, intestinal flora disorders, environmental factors, and an excessive immune response [14]. Chronic colonic inflammation is associated with increased oxidative stress and disruption of the intestinal homeostasis [5, 6]. Thus, it is necessary to determine the potential mechanism of increased oxidative stress in patients with IBD [7].…”
Section: Introductionmentioning
confidence: 99%